2019
DOI: 10.1093/rpd/ncz196
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Induced Plasmid Dna Damage: Effect of Concentration and Length

Abstract: Plasmid DNA is commonly used as a simpler substitute for a cell in studies of early effects of ionizing radiation because it allows to determine yields of primary DNA lesions. Experimental studies often employ plasmids of different lengths, in different concentrations in the aqueous solution. Influence of these parameters on the heavy-ion induced yields of primary DNA damage has been studied, using plasmids pUC19 (2686 bp), pBR322 (4361 bp) and pKLAC2 (9107 bp) in 10 and 50 ng/μl concentration. Results demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Damage of plasmid DNA due to exposure to oxidizing and ionizing agents is shown to be a good approximation for cell DNA damage before preparation processes start. ,, The effect of an argon plasma jet coupled with aerosol and VUV/UV radiation from plasma was examined on plasmid DNA. Normally, commercial plasmid DNA (>90%) exists in supercoiled (SC) form.…”
Section: Resultsmentioning
confidence: 99%
“…Damage of plasmid DNA due to exposure to oxidizing and ionizing agents is shown to be a good approximation for cell DNA damage before preparation processes start. ,, The effect of an argon plasma jet coupled with aerosol and VUV/UV radiation from plasma was examined on plasmid DNA. Normally, commercial plasmid DNA (>90%) exists in supercoiled (SC) form.…”
Section: Resultsmentioning
confidence: 99%
“…Using different concentration of plasmids, no significant difference in DNA damage was observed by Brabcová et al. 21 Kong et al. 56 indicates that the proportion between free radical damage and direct ionizing damage is independent of DNA concentration when the DNA concentration is under a certain value (50 ng/μL).…”
Section: The Dna Plasmid As a Biodosimeter For Nano‐radiosensitizatio...mentioning
confidence: 92%
“…Studies showed that, the number of SSBs per DNA molecule is linearly proportional to plasmid size. 54 , 57 According to Brabcová et al., 21 radiation‐induced plasmid DNA damage within plasmids is influenced by plasmid length. Taken together and based on their results, they confirmed that longer plasmid molecules are more radiosensitive.…”
Section: The Dna Plasmid As a Biodosimeter For Nano‐radiosensitizatio...mentioning
confidence: 99%
See 1 more Smart Citation
“…[1] Plasmid DNA is commonly used as a simpler substitute for a cell in studies of early effects of ionizing radiation, because it allows to determine yields of primary DNA lesions. [2] Numerous methods for enhancing the stability of recombinant organisms have been discovered. [3] Stable host-vector connections can be attained by adjusting the genetic makeup of recombinants as well as the environment under which the organisms are cultured.…”
Section: Introductionmentioning
confidence: 99%